Longevity of vaccine protection: Immunological mechanism, assessment methods, and improving strategy. Issue 1 (31st January 2022) - Chen, Zhian; Gao, Xin; Yu, Di
Abstract: Vaccination represents one of the most important achievements in modern medicine. During the era of COVID‐19 pandemic, the successful vaccination for SARS‐COV‐2 is the major hope to bring the society back to normal. However, although vaccines, such as for smallpox and poliomyelitis, can trigger life‐long protection in individuals and help to generate the herd immunity resulting in the eradication of pathogens, other vaccines, with seasonal influenza vaccine as a case in point, are unable to induce sustained immunity so that repeated vaccination is required. As most vaccines were developed empirically, the immunological mechanism underlying the longevity of vaccine‐induced protection remains only partially understood. In this review, we first describe vaccine‐induced humoral immune response in which long‐lived plasma cells and memory B cells are produced. We then summarise methods using immunological correlates of protection to assess the longevity of vaccine efficacy and provide the evidence and knowledge for the duration of protection by current vaccines. Last, we discuss rationale and strategies to improve the duration of vaccine protection by targeting vaccine immunogenicity, antibody affinity, avidity and prime‐boost scheme. Abstract : Vaccination represents one of the most important achievements in modern medicine. This review summarises the methods using immunological correlates to assess the longevity of vaccine‐mediated immune protection. The evidence and knowledge for the protection duration by current vaccines, as well as the strategies to improve future vaccines are discussed.